Genetic dissection of nonconventional introns reveals codominant noncanonical splicing code in Euglena - Toshihisa Nomura; June-Sik Kim; Osamu Iwata; Koji Yamada; Kohei Atsuji; Yukiko Uehara-Yamaguchi; Takuhiro Yoshida; Komaki Inoue; Kotaro Takahagi; Tetsuya Sakurai; Kazuo Shinozaki; Takuro Ito; et al. (Proceedings of the National Academy of Sciences, 2025)
Pre-mRNA splicing is essential for eukaryotic gene expression and is achieved through the accurate recognition of exon–intron boundaries. Although nonconventional introns, which do not follow the conventional GT-AG splicing rule, have been identified in several species, these introns are typically rare in any given genome. Here, we demonstrate the widespread occurrence of nonconventional introns (71.8% of all introns) in the Euglena agilis genome and identify consensus motifs at these nonconventional exon–intron boundaries. We assessed the splicing efficiency of nonconventional introns and variants with point mutations via genomic knock-in within the second exon of Glucan synthase-like 2 in Euglena gracilis and genetically defined the sequence signature (5′-N 3 CDG-/-CH′GN 5–6 |R exon -3′) required for their proper splicing. This signature is present in 61.2% of all nonconventional introns detected in the E. agilis genome. Accordingly, we present a noncanonical splicing code for Euglena introns, highlighting the global coexistence of dual splicing rules for conventional and nonconventional introns.